The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/aoc.4815
|View full text |Cite
|
Sign up to set email alerts
|

Formation of CaCO3 deposits on OMS‐2 surface to synergistically promote peroxymonosulfate activation and organic dyes degradation

Abstract: The development of green and efficient catalysts for peroxymonosulfate (PMS) activation and organic pollutants degradation has received widespread attention. In this study, the hybrid CaCO 3 /OMS-2 catalysts were prepared by a simple precipitation approach and characterized by X-ray powder diffraction, N 2 adsorption-desorption, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and cyclic voltammetry. It was found that deposition of CaCO 3 on OMS-2 surface can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Second, according to the previous literature, bare CaCO 3 can activate PMS to degrade organic pollutants, and it may contribute to the overall catalytic activity of AgFeO 2 @CaCO 3 . [ 34 ] As shown in Figure 3b, ≈20.5% of the RhB was removed after 60 min by CaCO 3 in the presence of PMS. Last, studies have demonstrated that hydroxyl groups in catalysts can enhance their catalytic activity in activating PMS.…”
Section: Resultsmentioning
confidence: 97%
“…Second, according to the previous literature, bare CaCO 3 can activate PMS to degrade organic pollutants, and it may contribute to the overall catalytic activity of AgFeO 2 @CaCO 3 . [ 34 ] As shown in Figure 3b, ≈20.5% of the RhB was removed after 60 min by CaCO 3 in the presence of PMS. Last, studies have demonstrated that hydroxyl groups in catalysts can enhance their catalytic activity in activating PMS.…”
Section: Resultsmentioning
confidence: 97%
“…[30][31][32] The Ca 2p spectrum shows two peaks at 350.1 and 346.3 eV, revealing the presence of CaCO 3 (Figure S8b, Supporting Information). [33] Furthermore, the C 1s spectrum displays two peaks at 284.6 eV (C─C) and 289 eV (O─C═O) (Figure S8c, Supporting Information). [34] The O 1s spectrum can be deconvoluted into a strong peak of C ¼ O at 530.8 eV and a relatively weak peak of Cu─O at 529.3 eV (Figure S8d, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%